2015
DOI: 10.1108/ilt-01-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

An experiment on wear particle’s texture analysis and identification by using deterministic tourist walk algorithm

Abstract: Purpose – This study aims to use a deterministic tourist walk to build a system that can identify wear particles. Wear particles provide detailed information about the wear processes taking place between mechanical components. Identification of the type of wear particles by image processing and pattern recognition is key to effective online monitoring algorithm. There are three kinds of particles that are particularly difficult to distinguish: severe sliding wear particles, fatigue spall partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The deterministic tourist walk-based approach has been used to build a system for the identification of wear particles [106]. Wear particles give information on the wear processes taking place between mechanical components.…”
Section: ) Examples Of Applicationsmentioning
confidence: 99%
“…The deterministic tourist walk-based approach has been used to build a system for the identification of wear particles [106]. Wear particles give information on the wear processes taking place between mechanical components.…”
Section: ) Examples Of Applicationsmentioning
confidence: 99%
“…Wang [20] used principal component analysis to optimize the characteristic parameters of wear particles and then distinguish wear particles with Grey relational analysis. Other methods have also been used in this area, such as classification and regression trees [11], deterministic tourist walks [21], the AdaBoost algorithm [22], and extreme learning machines [23]. To the best of our knowledge, most identification models for wear particles are based on 2D characteristics, and very few researches have used 3D characteristics to identify categories of wear particles [24].…”
Section: Introductionmentioning
confidence: 99%
“…The parameters that define wear particles such as their quantity, shape, and size reflect the wear modes, wear mechanisms, and severity associated with their generation [4]. Wear debris contained in the lubrication oil carry detailed and important information about the condition of the machine [5]. The particle characteristics are sufficiently specific so that the operating wear modes within the machine may be determined, allowing prediction of the imminent behavior of the machine [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the work focused on how to identify wear particles [1]. It is reported that antcolony algorithm [9], deterministic tourist walking [5], and fuzzy -means algorithm [10] can be used to identify wear particles. Also, in [11], attempts had been made to identify adhesive fatigue and abrasive particles using area, perimeter, and elongation parameters; study shows that these simple parameters can be effective for certain types of wear particles such as abrasive particles and sphere like fatigue particles.…”
Section: Introductionmentioning
confidence: 99%